2009
DOI: 10.1096/fj.08-119388
|View full text |Cite
|
Sign up to set email alerts
|

Sex of the cell dictates its response: differential gene expression and sensitivity to cell death inducing stress in male and female cells

Abstract: Sexual dimorphisms are typically attributed to the hormonal differences arising once sex differentiation has occurred. However, in some sexually dimorphic diseases that differ in frequency but not severity, the differences cannot be logically connected to the sex hormones. Therefore, we asked whether any aspect of sexual dimorphism could be attributed to chromosomal rather than hormonal differences. Cells taken from mice at d 10.5 postconception (PC) before sexual differentiation, at d 17.5 PC after the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
103
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(111 citation statements)
references
References 31 publications
7
103
0
1
Order By: Relevance
“…Cells derived from day 10.5 mouse embryos and grown in culture show similar patterns and rates of cell division irrespective of chromosomal sex but differ in their sensitivity to applied insults (e.g. ethanol) with female lineages showing higher rates of cell death (Penaloza et al 2009). …”
Section: Genetic and Morphological Differences In Developmentmentioning
confidence: 99%
“…Cells derived from day 10.5 mouse embryos and grown in culture show similar patterns and rates of cell division irrespective of chromosomal sex but differ in their sensitivity to applied insults (e.g. ethanol) with female lineages showing higher rates of cell death (Penaloza et al 2009). …”
Section: Genetic and Morphological Differences In Developmentmentioning
confidence: 99%
“…"To tell you the truth, it's actually kind of surprising how big an effect of sex chromosomes we've been able to see, " says Arnold. He and his colleagues have shown 17 that the dose of X chromosomes in a mouse's body can affect its metabolism, and studies in a lab dish suggest 18 …”
Section: Cellular Sexmentioning
confidence: 99%
“…However, this proposal does not take into account the many important effects of perinatal secondary sexual differentiation and may only be true for a minority of sex-related traits. Recently, it has been demonstrated that sexual dimorphism can be attributed also to the sex chromosomes (76) . Using cells that were harvested from embryonic mice before sexual differentiation on day 10 .…”
Section: Transduction Of Environmental Signals To the Epigenetic Machmentioning
confidence: 99%